Princ??pios pol??ticos de liberdade: pr??tica pedag??gica libert??ria em S??o Paulo (1912-1919) - Costa, Marcelo Luiz da (2011)
This research aims to study the main activities developed while teaching practices in the Modern School of S??o Paulo, Brazilian experience of the anarchist movement, between 1912 and 1919. The libertarian pedagogy, which took root in European socialism and anarchism, had impacts in Brazil with the presence of foreign immigrants, however, its historical development had the militancy of brazilians or foreigners settled here. To do so, are raised, historic paths traveled by the brazilian labor movement, detecting some of its landmarks, the First Brazilian Worker s Congress in 1906, the intent of the implementation of school workers, free or rationalists, in general, from the late nineteenth century and, in particular, in the early twentieth century, as well as the historical context of the rise time of the Modern School, founded by anarchists as a model and had to face John Penteado, a professor anarchist coming from the interior of Sao Paulo. Records of such practices are reported in the school newspaper The Beginning and Modern School Bulletin. These records disclose not only the presence of anarchist ideology that education, but also the same means of action also employed by the movement, as the conference and the public demonstration, in addition to the activities highlighted the libertarian principles that, therefore, by the hand of the inner core anarchists they acquired their condition of existence on national soil.